(untitled) (Iranian Journal of Kidney Diseases, 2020)
Introduction. Calcium channel blockers (CCBs) are commonly used agents in the treatment of hypertension as part of monotherapy or combination therapy. Peripheral edema is the most common side effect that requires discontinuation or replacement of treatment. Some studies in the literature have shown that long-acting dihydropyridine type CCBs lead chylous ascites in peritoneal dialysis patients. However, amlodipine-associated serous ascites cases are not available in the literature. Case Report. In this case report, we describe a rare case of amlodipine induced massive ascites in a 30-year-old male with renal transplantation. Conclusion. We aimed to create awareness that pharmacologic causes should be considered in cases of ascites of unknown aetiology.